Clinical status and evolution in moyamoya: which angiographic findings correlate?. Issue 1 (30th October 2019) - Rosi, Andrea; Riordan, Coleman P; Smith, Edward R; Scott, R Michael; Orbach, Darren B
Abstract: Moyamoya is a progressive steno-occlusive cerebrovascular pathology of unknown aetiology that usually involves the terminal portions of the internal carotid arteries and/or the proximal portions of the anterior and middle cerebral arteries bilaterally. The pre-operative Suzuki staging system and post-operative Matsushima grade are nearly universally used markers of natural history and surgical revascularization results, respectively, but their correlation with clinical and radiographic manifestations of moyamoya has not been systematically evaluated in a large cohort. This study evaluated the strength of correlations between pre- and post-operative angiographic parameters and clinical status among paediatric patients with moyamoya. The participants included 58 patients of mean age 11 years at the time of surgery who underwent bilateral indirect revascularization in the same procedure at Boston Children's Hospital, between January 2010 and December 2015. All included patients had available pre-operative and 1-year post-operative digital subtraction angiography. Clinical data included presenting symptoms, degree of functional incapacity, and peri-operative and long-term complications. Radiographic data included pre-operative Suzuki stage, degree of arterial stenosis, a novel collateral score, the presence of hypovascular territories on digital subtraction angiography, and post-operative Matsushima grade and evolution of stenosis. Chi-squared test and Pearson coefficient were used for correlation studies for categorical variables and Spearman's rho was used for correlation studies for continuous variables. Results showed that Suzuki stage, collateral score and degree of stenosis were insufficient to predict clinical presentation, pre-operative incapacity and radiographic presentation, whereas the presence of hypovascular territories was correlated with all of these. At 1-year follow-up, Matsushima grade was insufficient for predicting peri-operative or long-term complications, nor did it correlate with post-operative incapacity. The presence of hypovascular territories at 1-year follow-up was correlated with the incidence of post-operative ischaemic symptoms. Abstract : The authors present a large series of paediatric patients with bilateral moyamoya who underwent surgical revascularization and who had pre-operative and post-operative angiography. Clinical status and evolution was not found to correlate to common angiographic markers or severity scales but rather to angiographically defined hypovascular regions. Graphical Abstract: